Peningkatan Pengetahuan Siswa SMKN 2 Bandar Lampung Tentang Bahaya Rokok Melalui Penyuluhan - Nisrina Aulia Amirah; Dyah Wulan Sumekar; Tri Umiana Soleha; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2020)
Smoking is a global health problem, almost every country experiences an increase in adolescent smokers. Indonesia is the third largest country with the highest number of smokers after China and India. Various methods have been used to reduce the number of smokers at an adolescent. One effective method of preventing an increase in the number of adolescent smokers is counseling about cigarette risk knowledge. In preliminary research, we got there are around 90% of smoking students especially male students. The cause is lack adolescent knowledge against the dangers of smoking. This research aims to know the effect of counseling on cigarette risk knowledge in student SMKN 2 Bandar Lampung. It was carried out in April 2017, place in SMKN 2 Bandar Lampung. The results of the hypothesis with the values of the t-test paired obtained p = 0000 that indicate a difference of knowledge comparison before and after counseling on Students of SMKN 2 Bandar Lampung. So it can be inferred that the counseling intervention can increase cigarette risk knowledge on students SMKN 2 Bandar Lampung.